Utilization of Industrial Machine Waste Heat for Co-Generation Systems - Mochamad Saleh (Universitas Muhammadiyah Palu, 2025)
Waste heat generated from industrial machinery operations represents a significant yet underutilized energy resource, particularly in developing countries like Indonesia. This thermal energy, if properly harnessed, holds considerable potential for conversion into useful energy through the implementation of co-generation systems. Co-generation refers to the simultaneous production of electricity and heat from a single fuel source. Utilizing this system not only enhances overall energy efficiency but also contributes to reducing greenhouse gas emissions and lowering industrial operating costs. This study explores the potential use of industrial waste heat in Indonesia and assesses the feasibility of applying co-generation systems using locally adapted technologies aligned with national industrial conditions. The research methodology includes a combination of literature review, field observation, and interviews with industry practitioners. Findings reveal that co-generation systems can reduce primary energy consumption by up to 30% and improve thermal efficiency to over 70%. Moreover, this approach offers economic benefits by lowering energy expenses and enhancing industrial productivity. In conclusion, harnessing waste heat through co-generation presents a strategic pathway toward improving national energy efficiency and promoting industrial sustainability. Successful implementation will require strong policy support, fiscal incentives, technological innovation, and the development of skilled human resources.